The Effectiveness of Augmented Reality-Based Simulation Media for Fiber Optic Splicing in Vocational Network Technology Education - Annisa Saputri; Ta’ali Ta’ali; Giatman Giatman; Yeka Hendriyani (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop and evaluate an Augmented Reality (AR)-based simulation media for teaching fiber optic splicing in vocational network technology education. Using a Research and Development (R&D) approach with the 4D model (Define, Design, Develop, Disseminate), the product was validated by experts and tested for practicality and effectiveness through a one-group pretest–posttest design. The media obtained high validity scores (Aiken’s V = 0.85 for media and 0.97 for material), was categorized as very practical by teachers (98.31%) and students (89.52%) and showed significant improvement in learning outcomes (N-gain = 0.7115; p < 0.05). Unlike previous AR studies that mainly focus on conceptual science learning, this research integrates procedural vocational skills simulation with mobile-based AR to address limited access to expensive splicing equipment. The findings indicate that AR-based simulation can effectively enhance students’ procedural understanding and support technology-integrated vocational pedagogy